Evaluating healthy workplace in geothermal industry - Febrian, Nurtito Wahyu (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The geothermal industry is located in mountainous areas and far from urban centers that are at risk of danger. Hazard management is one aspect of occupational safety health management, including occupational environmental health. Therefore, this study aims to evaluate the healthy workplace in geothermal industry. Observation and measurement technique are used to determine the light intensity, noise, humidity and temperature in all room in the industry. The results state that there are three rooms that did not meet the standard, the noisy still eligible both for offices (65dBA) and PLTP (85 dBA), the humidity is quite high (60%) and the average temperature is 15-20oC. Most of the indicators are still below the limit value based on the company and local regulations. Pengukuran aspek fisik monitoring kesehatan lingkungan kerja sudah memperoleh hasil yang baik. Namun, masih ada beberapa lokasi lingkungan kerja yang perli dilakukan perbaikan lagi dari segi pencahayaan dengan penggantian jenis lampu LED, dan pengaturan suhu dan kelembapan ruang. The assessment of healthy workplace is needed to improve the well-being of the workers in geothermal industry.